2010
DOI: 10.1039/b922749k
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of electron deficient guanine radical species in plasmid DNA by tyrosine derivatives

Abstract: Guanine bases are the most easily oxidized sites in DNA and therefore electron deficient guanine radical species are major intermediates in the direct effect of ionizing radiation (ionization of the DNA itself) on DNA as a consequence of hole migration to guanine. As a model for this process we have used gamma-irradiation in the presence of thiocyanate ions to generate single electron oxidized guanine radicals in a plasmid target in aqueous solution. The stable species formed from these radicals can be detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Model studies showed that the rate constant for dG •+ reduction by tyrosine is >10 6 greater than that for trapping by H 2 O (∼6 × 10 4 s −1 , pH 7). 24,35,36 This suggests that dG •+ reduction by tyrosine within a NCP can compete with deprotonation and hole transfer. 36,37 Hole reduction in DNA by Tyr41 was initially probed by examining the effect of a deuterated buffer on HTE (Figure S12, 13).…”
Section: Htementioning
confidence: 99%
See 2 more Smart Citations
“…Model studies showed that the rate constant for dG •+ reduction by tyrosine is >10 6 greater than that for trapping by H 2 O (∼6 × 10 4 s −1 , pH 7). 24,35,36 This suggests that dG •+ reduction by tyrosine within a NCP can compete with deprotonation and hole transfer. 36,37 Hole reduction in DNA by Tyr41 was initially probed by examining the effect of a deuterated buffer on HTE (Figure S12, 13).…”
Section: Htementioning
confidence: 99%
“…In addition, hole transfer can be suppressed by histone tyrosine residues that rapidly reduce dG •+ . 23,24 Consequently, HTE within a NCP may depend on the location of the DNA over which hole migration occurs with respect to the protein structure, in addition to the DNA sequence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the fact that guanine is the most easily oxidizable base in DNA due to its lowest potential 47,48 and it also tends to be oxidized to form stable radical cations. 49 The obtained results demonstrated the satisfactory selectivity of the proposed CoOx nanoower-modied Al electrode toward the electrocatalytic oxidation of guanine at a remarkable reduced over-voltage. Thus, the proposed electrode could be a practical sensor for the determination of guanine in an assortment of various common oxidizable species without separation.…”
Section: Interference Study and Selectivitymentioning
confidence: 64%
“…13 The candidate transient lesions include guanidine radical cations G + which results in formation of stable products such as 8-oxoguanine. 14 This mode of protection is quite distinct from the indirect mode of radioprotection that is provided by the radioprotector amifostine 5, a prodrug of the corresponding aminothiol, which like many other aminothiols, act principally by hydroxyl radical scavenging. 15 As part of a program aimed at discovering more potent radioprotectors we considered the incorporation of the chalcogens S, Se and Te to replace one or both of the N-H groups in the bisbenzimidazole backbone of 1-4 and related molecules.…”
Section: Introductionmentioning
confidence: 99%